Dose Selection for Ceftibuten Combined with Avibactam Tomilopil, a Potential Oral Alternative to Carbapenems for Patients with Complicated Urinary Tract Infections - Siddhee A. Sahasrabudhe; Satoshi Shoji; Abhijeet S. Jakate; Bisrat K. Abraham; Sima S. Toussi; Benjamin J. Maligalig; Amanda S. Darekar; Sakambari Tripathy; Constantino Kantaridis; Josue K. Mfopou; Oxana Selivanova; Arthur Bergman; et al. (The Journal of Clinical Pharmacology, 2026)
Abstract There are currently no oral treatment options for infections caused by extended spectrum β‑lactamase‐producing Enterobacterales. Avibactam tomilopil, a novel oral prodrug of avibactam, is being developed in combination with the oral cephalosporin, ceftibuten, as a potential treatment for patients with complicated urinary tract infections (cUTIs). The safety, tolerability, and pharmacokinetic profiles of single and multiple doses of avibactam tomilopil (900 to 1350 mg) and ceftibuten (400 to 1600 mg), alone and/or in combination were evaluated in three Phase 1 trials in healthy participants. Avibactam tomilopil was rapidly metabolized to active avibactam and plasma avibactam exposure increased proportionately with dose. Both avibactam and cis‐ceftibuten had similar plasma half‐lives, and were predominantly renally excreted. While there was negligible food effect on ceftibuten exposures, plasma avibactam exposure in the fed state for a fixed‐dose combination ceftibuten‐avibactam tomilopil tablet was higher compared with the fasted state. Based on joint probability of target attainment simulations using a simultaneous oral ceftibuten‑avibactam tomilopil population pharmacokinetic model, a tablet formulation ceftibuten 400 mg + avibactam tomilopil 1200 mg dosed every 8 h without regard to food is proposed for Phase 3 evaluation in adult patients with cUTIs. Trial registration: NCT03931876; NCT05554237; NCT06593054.